In Operando and Local Estimation of the Effective Humidity of PEMFC Electrodes and Membranes. Issue 14 (14th November 2017) - Gaumont, Thomas; Maranzana, Gaël; Lottin, Olivier; Dillet, Jérôme; Guétaz, Laure; Pauchet, Joël
Abstract : An electrochemical impedance model is developed to describe the impedance response of a volumetric electrode accounting for proton migration in the absence of oxygen transport limitation. It is used to fit experimental impedance spectra in H2 /O2 configuration in order to estimate the protonic resistance of the electrode. Spatial resolution is achieved using a segmented cell, in dry, partially humidified and fully humidified conditions and at different cell currents. The local effective humidity in the cathode catalyst layer (CCL) and in the membrane are deduced from a correlation relating the protonic resistance measured in H2 /N2 configuration to the relative humidity. Self-humidification of a cell operated in counter flow with dry oxygen is monitored using this technique, and the contributions of the membrane and of the CCL to the overall ohmic losses are eventually estimated.